1997
DOI: 10.1046/j.1464-410x.1997.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Desmopressin for nocturnal enuresis: urinary osmolality and response

Abstract: Objective To measure the eÂect of intranasal desmopres-The response was better in older patients and in those with less frequent enuresis. The mean and peak urisin (1-deamino 8-d-arginine vasopressin, DDAVP) on urine osmolality in a group of patients with persistent nary osmolality of the morning urine samples were higher while on treatment with DDAVP compared primary enuresis, and to determine whether changes in osmolality can the predict response to treatment.with placebo, but this diÂerence was not statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 1 publication
0
8
0
2
Order By: Relevance
“…A low functional bladder capacity, relative polyuria, and urodynamic abnormalities, such as bladder instability and dysfunctional voiding, may result in frequent urination. A low functional bladder capacity occurs in almost all enuretic children, and to increase the functional bladder capacity is, therefore, a therapeutic goal in patients having enuresis [1,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…A low functional bladder capacity, relative polyuria, and urodynamic abnormalities, such as bladder instability and dysfunctional voiding, may result in frequent urination. A low functional bladder capacity occurs in almost all enuretic children, and to increase the functional bladder capacity is, therefore, a therapeutic goal in patients having enuresis [1,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…A good success rate was found when using both DDAVP and an alarm program in children who had previously failed when they had tried either of these methods separately (Folwell et al, 1997;Moffatt, 1997). Bath et al (1996) concluded that if a course (in this case, four months) with an enuretic alarm is unsuccessful, it is better to consider the use of the dry-bed training technique instead of Desmopressin for those children under 9-years-old.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…18 Some authors have found a positive correlation between age and response to desmopressin treatment, while others have noted a positive correlation between fewer baseline wet nights and improved response to desmopressin. 4,5,12 The first observation is certainly valuable, since one can assume that younger children are more prone to have a small FBC and/or bladder overactivity, which is a well known factor behind inadequate desmopressin response. 4,19 Our data support this observation, since the MNE-SB group was significantly younger than the MNE-NP group.…”
Section: Discussionmentioning
confidence: 99%